US volatility cycles of output and inflation, 1919 - 2004: A money and banking approach to a puzzle - Szilárd Benk; Max Gillman; Michal Kejak (Cardiff University, Cardiff Business School, 2008)
The post-1983 moderation coincided with an ahistorical divergence in the money aggregate growth and velocity volatilities away from the downward trending GDP and inflation volatilities. Using an endogenous growth monetary DSGE model, with micro-based banking production, enables a contrasting characterization of the two great volatility cycles over the historical period of 1919-2004, and enables this puzzle to be addressed more easily. The volatility divergence is explained by the upswing in the credit volatility that kept money supply variability from translating into inflation and GDP volatility.
Keywords: E13; E32; E44; 330; volatility; money and credit shocks; growth; inflation; Gesamtwirtschaftliche Produktion; Inflationsrate; Volatilität; Kreditmarkt; Geldangebot; Dynamisches Gleichgewicht; USA